Fear of Childbirth in Nulliparous Women - Hendrix, Yvette M. G. A.; Baas, Melanie A. M.; Vanhommerig, Joost W.; de Jongh, Ad; Van Pampus, Maria G. (Frontiers in Psychology, 2022)
Purpose: The relation between fear of childbirth (FoC) and gestational age is inconclusive, and self-reported need for help regarding this fear has never been investigated. This study aimed to determine the prevalence and course of FoC according to gestational age, to identify risk factors for the development of FoC, the influence of this fear on preferred mode of delivery and self-reported need for help. Methods: Nulliparous pregnant women of all gestational ages completed an online survey. The study consisted of a cross-sectional and a longitudinal analysis. Women who completed the survey in the first or second trimester (T0) were approached again in their third trimester (T1). The Wijma Delivery Expectancy Questionnaire Version A (W-DEQ A) was used with a cut-off score ≥ 85 to define presence of fear of childbirth. Questionnaires indexing social support, anxiety, symptoms of depression, preferred mode of delivery, and self-reported need for help were included. Results: In total, 364 women were enrolled at T0, and 118 out of 184 eligible women were included in the longitudinal analysis. Point prevalence of FoC at T0 was 18.4% with no significant difference between trimesters. In the longitudinal sample, prevalence of FoC decreased from 18.6% (T0) to 11.0% (T1), P=0.004. Although mean scores for FoC decreased significantly, P<0.001, scores increased in 41 (34.7%) women. Presence of FoC was associated with elevated anxiety, less family support, prenatal care of the obstetrician by choice, preference for a cesarean section, and for pain relief. Women with FoC were more likely to actively seek for help compared to women without FoC. Conclusions: While FoC is common in each trimester, prevalence decreases over the course of pregnancy. Women with FoC are often actively seeking for help, suggesting that this fear should be addressed better, and help should be offered accordingly.